CLinical Assessment of WEB device in Ruptured aneurYSms (CLARYS): results of 1-month and 1-year assessment of rebleeding protection and clinical safety in a multicenter study. (7th September 2021) - Spelle, Laurent; Herbreteau, Denis; Caroff, Jildaz; Barreau, Xavier; Ferré, Jean-Christophe; Fiehler, Jens; Januel, Anne-Christine; Costalat, Vincent; Liebig, Thomas; Bourcier, Romain; Möhlenbruch, Markus; Berkefeld, Joachim; et al.
Abstract : Background: The primary goal of the CLARYS study is to assess the protection against rebleeding when treating ruptured bifurcation aneurysms with the Woven EndoBridge (WEB) device. Methods: The CLARYS study is a prospective, multicenter study conducted in 13 European centers. Patients with ruptured bifurcation aneurysms were consecutively included between February 2016 and September 2017. The primary endpoint was defined as the rebleeding rate of the target aneurysm treated with the WEB within 30 days postprocedure. Secondary endpoints included periprocedural and postprocedural adverse events, total procedure and fluoroscopy times, and modified Rankin Scale score at 1 month and 1 year. Results: Sixty patients with 60 ruptured bifurcation aneurysms to be treated with the WEB were included. A WEB device was successfully implanted in 93.3%. The rebleeding rate at 1 month and 1 year was 0%. The mean fluoroscopy time was 27.0 min. Twenty-three periprocedural complications were observed in 18 patients and resolved without sequelae in 16 patients. Two of these complications were attributed to the procedure and/or the use of the WEB, leading to a procedure/device-related intraoperative complication rate of 3.3%. Overall mortality at 1 month and 1 year was 1.7% and 3.8%, respectively and overall morbidity at 1 month and 1 year was 15% and 9.6%, respectively. WEB-related 1-month and 1-year morbidity and mortality was 0%. Conclusions: The interim results of CLARYS show that the endovascular treatment of ruptured bifurcation aneurysms with the WEB is safe and effective and, in particular, provides effective protection against rebleeding. It may induce profound change in the endovascular management of ruptured bifurcation aneurysms.